Tanah untuk Pasar: Neoliberalisme Hukum dalam Reforma Agraria Rezim Joko Widodo - Hamdhani, Ali Fikri; Hadiyantina, Shinta (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2025)
Upon his appointment as president, Joko Widodo prioritized agrarian justice through agrarian reform. Many individuals examine it through the lens of doctrinal studies, yet their focus remains on its execution. On the other hand, this study will look at the background and motives for the formation of Jokowi's agrarian reform, because in the history of the practice of agrarian reform from time to time, it has always been influenced by existing political-economic conditions. This study will ask key questions about the influence of the doctrine of neoliberalism on the encouragement of capitalist states and international institutions that have developed rapidly since the 1970s. The study method involves conducting socio-legal studies using a conceptual and historical approach, primarily obtaining data through literature reviews and government and non-government documents. This study shows that Jokowi's pattern of agrarian reform has not changed much in principle from previous eras, which were based on the workings of the land mechanism for the market system. Since the second period, this has been strengthened through job creation products that regulate norms regarding land banks and land tenure rights (HPL), thereby benefiting investors. Instead of promoting significant redistribution, this approach reinforces the privatization and deregulation of land, which aligns with the principles of neoliberalism. This condition has implications for the tendency to use repressive methods, as it prioritizes the legality of the land market over resolving the problem of land tenure inequality. Salah satu agenda prioritas Joko Widodo (Jokowi) ketika dilantik menjadi Presiden adalah keadilan agraria melalui reforma agraria. Cukup banyak yang mengkajinya melalui studi doctrinal, namun terbatas sekedar pada pelaksanaan. Sebaliknya, studi ini akan melihat latar belakang dan motif terbentuknya reforma agraria Jokowi, karena dalam sejarah praktik reforma agraria dari masa ke masa, selalu terpengaruh dengan kondisi ekonomi-politik yang ada. Studi ini akan mengajukan pertanyaan kunci tentang pengaruh doktrin neoliberalisme dorongan negara kapitalis dan lembaga internasional yang berkembang pesat sejak 1970-an. Metode studi melalui kajian socio-legal dengan pendekatan konseptual dan sejarah, data diperoleh sekunder melalui kajian literatur, dokumen pemerintah maupun non-pemerintah. Studi ini menunjukkan pola reforma agraria ala Jokowi tidak banyak berubah secara prinsip dengan era-era sebelumnya, dimana berpijak pada cara kerja mekanisme tanah untuk sistem pasar. Hal ini menguat sejak periode keduanya melalui produk Cipta Kerja yang mengatur norma tentang Bank Tanah dan Hak Penguasaan Lahan (HPL) yang menguntungkan investor. Alih-alih redistribusi yang signifikan, cara kerja itu memperkuat privatisasi dan deregulasi atas tanah seperti prinsip dalam neoliberal. Kondisi itu berimplikasi pada kecenderungan cara-cara represif dengan memprioritaskan legalitas pasar tanah dibandingkan menyelesaikan masalah ketimpangan penguasaan tanah.